2017
DOI: 10.1177/2325957417729750
|View full text |Cite
|
Sign up to set email alerts
|

Do Persons Living with HIV Continue to Fill Prescriptions for Antiretroviral Drugs during a Gap in Care? Analysis of a Large Commercial Claims Database

Abstract: The significance of a gap in HIV care depends, at least partially, on whether patients continue to fill prescriptions for antiretroviral (ARV) drugs during the gap in care. We used a billing claims database to determine the proportion of persons who filled 1 prescription for ARV drugs during a gap in care (no clinic visit in >6 months). Persons were stratified into 3 groups: “never” (prescriptions never filled), “sometimes” (prescriptions filled >0%-<100% of months), and “always” (prescriptions filled monthly)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A recent analysis of a large billing claims database found that the proportion of persons who filled a prescription each month, throughout the entire length of gaps of more than 6 months, significantly decreased as the gap length increased. 22 This finding suggests that longer gaps do contribute more failures to refill medications than shorter gaps.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of a large billing claims database found that the proportion of persons who filled a prescription each month, throughout the entire length of gaps of more than 6 months, significantly decreased as the gap length increased. 22 This finding suggests that longer gaps do contribute more failures to refill medications than shorter gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Using a median value of 19%, we changed this to a monthly probability of each person taking a gap that month, 1e −0.19 * (1/12) = 0.016. Because 69% of those who experienced a gap never filled their prescriptions during the gap, 26 we assumed they were not virally suppressed and did not accrue costs (except for non-HIV medications). The duration of the gap was selected from a truncated normal distribution with a mean of 3 months, a standard deviation of 3 months, and lower and upper bounds of 1 and 12 months.…”
Section: Methodsmentioning
confidence: 99%